Leaf Orientation as Part of the Leaf Developmental Program in the Semi-Deciduous Shrub, Cistus albidus L.: Diurnal, Positional, and Photoprotective Effects During Winter - Pérez-Llorca, Marina; Casadesús, Andrea; Müller, Maren; Munné-Bosch, Sergi (Frontiers in Plant Science, 2019)
Mediterranean ecosystems harbor a very important part of Earth’s biodiversity, and they are a conservation priority due to the effects of global change. Here, we examined the performance of the semi-deciduous shrub Cistus albidus under Mediterranean conditions during winter, including changes in leaf angle governed by diurnal, seasonal, and positional effects and their relationship with winter photoinhibition and photoprotection. We found marked diurnal variations in leaf angle during the day in autumn, which disappeared as the photoperiod shortened during winter due to a progressive decrease in the predawn leaf angle from November to January. During this period, auxin contents decreased, while those of melatonin increased, and the Fv/Fm ratio, chlorophyll, and tocopherol contents kept unaltered, thus indicating the absence of photoinhibitory damage. A marked decrease in the leaf angle toward the shoot apex occurred during winter, which was associated with slightly higher Fv/Fm ratios. An analysis of the inter-individual variability and sun orientation effects on leaf movements in a population growing in the Montserrat mountains revealed a very marked variability of 46.8% in the leaf angle, while Fv/Fm ratio showed a variation of 7.5% only. West orientation, which was associated with reduced leaf temperatures, but with no differences in the photosynthetic photon flux density, led to enhanced tocopherol contents, while leaf angle, Fv/Fm ratio, chlorophyll, auxin, and melatonin contents kept unaltered. It is concluded that (1) C. albidus has very effective and fine-regulated photoprotection mechanisms, including an adequate orientation of decussate leaves as part of the developmental program, (2) leaf angle is modulated on a diurnal and seasonal basis, thus contributing to prevent photoinhibition as a first line of defense, and (3) enhanced tocopherol contents help withstand combined high light with low temperature stress in C. albidus growing at high elevation.